The Changing family life cycle : a framework for family therapy - Carter, Elizabeth A.; McGoldrick, Monica (Gardner Press, 1988)
This book - a provocative examination of family development and the variables that affects its course - emphasizes the changes in that life cycle as we move toward the 21st century. It offers essential guidance in understanding what happens in families in terms of the flow of live over the generations. The current edition provides a more in-depth perspective on the impact of gender on family life at each stage of the life cycle and on cultural variations in life cycle patterns. In addition to updated statistics and an integration of findings from research since 1980 on families through the life cycle, several important new chapters are included. Among the topics considered: chronic illness, alcoholism, single-parent families, rituals, genograms, and the contrasting of the life cycle of the poor with that of the upper middle classes. The contributors bring to this work a variety of expertise, experience, and vision that together constitute an invaluable resource for both the student and the working therapist.